Pregnancy Located below the Internal Os ? Cervical and Caesarean Scar Ectopics (Journal of Enam Medical College, 2015)
Cervical pregnancy is an extremely rare condition with potential grave consequences if not diagnosed early and treated properly. Here we report two cases of early cervical ectopic pregnancy with a history of previous one caesarean section. One case severely bled during evacuation and curettage and was successfully treated by hysterotomy followed by digital separation of product of conception. Another case was managed conservatively by medical method with injectable methotrexate.J Enam Med Col 2015; 5(2): 118-121